Effective nurse–patient relationships in mental health care: A systematic review of interventions to improve the therapeutic alliance. (February 2020) - Hartley, Samantha; Raphael, Jessica; Lovell, Karina; Berry, Katherine
Abstract: Background: Therapeutic alliance is a core part of the nursing role and key to the attainment of positive outcomes for people utilising mental health care services. However, these relationships are sometimes difficult to develop and sustain, and nursing staff would arguably benefit from evidence-based support to foster more positive relationships. Objectives: We aimed to collate and critique papers reporting on interventions targeted at improving the nurse–patient therapeutic alliance in mental health care settings. Design: Systematic literature review. Data sources: The online databases of Excerpta Medica database (Embase), PsycINFO, Medical Literature Analysis and Retrieval System Online (MEDLINE) and Cumulative Index of Nursing and Allied Health Literature (CINAHL) were searched, eligible full text paper references lists reviewed for additional works and a forward citation search conducted. Review methods: Original journal articles in English language were included where they reported on interventions targeting the nurse–patient therapeutic relationship and included a measure of alliance. Data were extracted using a pre-determined extraction form and inter-rater reliability evaluations were conducted. Information pertaining to design, participants, interventions and findings was collated. The papers were subject to quality assessment. Results: Relatively few eligible papers ( n = 8) were identified, highlighting the limitations of the evidence base in this area. A range of interventions were tested, drawing on diverse theoretical and procedural underpinnings. Only half of the studies reported statistically significant results and were largely weak in methodological quality. Conclusions: The evidence base for methods to support nursing staff to develop and maintain good therapeutic relationships is poor, despite this being a key aspect of the nursing role and a major contributor to positive outcomes for service users. We reflect on why this might be and make specific recommendations for the development of a stronger evidence base, with the hope that this paper serves as a catalyst for a renewed research agenda into interventions that support good therapeutic relationships that serve both staff and patients.